The incidence and prevention of Postoperative Venous Thrombosis - Joffe, Stephen Neal (Department of Surgery, 2017)
In the last few years a very high incidence of deep vein thrombosis has been reported in the literature. Venous thrombosis and its sequel, pulmonary embolus account for 12. 5% of all postoperative deaths and is the single greatest threat to recovery after surgical operations. This study was undertaken to investigate the incidence of postoperative deep vein thrombosis occurring at Groote Schuur Hospital using the newer methods of diagnosis. No previous similar study has been conducted in South Africa. The high-risk factors predisposing to venous thrombosis have been assessed and the techniques of diagnosis using Radio-active fibrinogen, Doppler ultrasound and Venography have been studied. The local findings reported in this study confirmed the high reported incidence. Methods of prevention of venous thrombosis using low doses heparin and sodium pentosan polysulphate have been assessed.